Effects of post activation potentiation on eccentric loading: Is it possible to do more repetitions after supra-maximal loading? - Sevilmis, E.; Atalag, O. (Journal of Human Sport & Exercise, 2019)
The aim of this study is to investigate the effects of Post Activation Potentiation (PAP) on muscular endurance performance. 42 physically active male participants (PAP Group n=32, Control Group n=10) who have at least 1 year of resistance training experience and exercise min. times/week, participated in this study. First testing session were the same for both Control and PAP group. On the first session, 1 Repetition Maximum (1RM) of subjects was found. 65% of the 1 RM was calculated to find the weight that was going to be used for the muscular endurance test. Subjects completed maximal number of repetitions with 65 % of their 1 RM. On the second test session which was done 48 hours after the first session, PAP group did eccentric loading with Bench Press with their 120 % of 1 RM than rest 8 minutes to elicit the effects of PAP. After the resting period, muscular endurance test with 65% of 1 RM and time under tension were recorded. No statistical difference was found between the number of repetitions that were done in the first and the second test session for control group (p>0.05). Whereas significant increase was found for the PAP group (p<0.05). No relationship between training experience and the number of increased repetitions was observed (p>0.05). As a result of this study, supra-maximal eccentric loading was found to be an effective method to elicit the effects of PAP on muscular endurance. Therefore, PAP protocols in resistance training sessions might be considered to be used for athletes who want to improve their muscular endurance performance.